Surface-microengineering for high-performance triboelectric tactile sensor via dynamically assembled ferrofluid template. (September 2021) - Zhang, Tingting; Wen, Zhen; Lei, Hao; Gao, Zhenqiu; Chen, Yunfeng; Zhang, Yi; Liu, Jingya; Xie, Yonglin; Sun, Xuhui
Abstract: Surface-microengineering of the active layer in triboelectric tactile sensor enables to effectively reduce the surface stiffness of the non-ideal planar triboelectric film and increase the contact area during the triboelectric process. In this work, a facile and dynamically controllable two-step method based on the unique characteristic of ferrofluid has been proposed to fabricate a high-performance self-powered triboelectric tactile sensor. Through adjusting the distance and rotating angle of magnet, ferrofluid spikes with different lengths and inclination angles ranging from 30° to 90° can be obtained. The adjustable microstructures distributed on the active layer were analyzed theoretically and verified experimentally, indicating the inclined and high microstructures can effectively facilitate the sensing performance. When the inclination angle of the microstructure is 30°, the sensitivity delivers 6.75 kPa −1 with pressure lower than 44 kPa, and keeps excellent linearity with the sensitivity of 3.01 kPa −1 even the detection pressure reaches 250 kPa. Simultaneously, the tactile sensor has a fast response/recovery time of 75 ms and 56 ms, respectively. Finally, it was demonstrated to adopt in the bionics robotic hands for weight perception and attached to various parts of the human body for detecting physiological activities with outstanding repeatability and stability. Graphical Abstract: A facile and dynamically controllable two-step method based on the unique characteristic of ferrofluid has been proposed to fabricate a high-performance self-powered triboelectric tactile sensor. The inclined and high microstructures can effectively facilitate the sensing performance. This sensor can be adopted in the bionics robotic hands or detect physiological activities with outstanding repeatability and stability. ga1 Highlights: Micro-engineered the dielectric surface of the tactile sensor with different inclination angles and length. The smaller inclination angle and more height are beneficial to the sensitivity and high sensitivity detection range. When the inclination angle is 30°, the sensitivity delivers 6.75 kPa −1 with pressure lower than 44 kPa.